KAJIAN STILISTIKA SASTRA LISAN TEMBANG ASAL SANGA DESA KABUPATEN MUSI BANYUASIN - Hetilaniar; Permana, Andi; Agustina, Juaidah (Universitas PGRI Palembang, 2022)
The problem in this study is how to study the stylistic oral literature of Tembang from Sanga Village, Musi Banyuasin Regency based on figurative language and imagery. The purpose of this study is to know and describe figurative language and imagery in the study of Tembang stilistics from Sanga Village, Musi Banyuasin Regency. . The source of data in this study is video recordings from youtube.